On certain multiple integral inequalities related to Hermite-Hadamard inequality - Yang, Gou-Sheng; Tseng, Kuei-Lin (Utilitas Mathematica, 2002)
In this paper, we establish several multiple integral inequalities related to Hermite-Hadamard inequality.